2016
DOI: 10.1021/acs.est.5b04436
|View full text |Cite
|
Sign up to set email alerts
|

Redox Reactions between Mn(II) and Hexagonal Birnessite Change Its Layer Symmetry

Abstract: Birnessite, a phyllomanganate and the most common type of Mn oxide, affects the fate and transport of numerous contaminants and nutrients in nature. Birnessite exhibits hexagonal (HexLayBir) or orthogonal (OrthLayBir) layer symmetry. The two types of birnessite contain contrasting content of layer vacancies and Mn­(III), and accordingly have different sorption and oxidation abilities. OrthLayBir can transform to HexLayBir, but it is still vaguely understood if and how the reverse transformation occurs. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 57 publications
18
103
0
Order By: Relevance
“…Such an evolution was consistent with previous studies (Elzinga, 2011(Elzinga, , 2016Lefkowitz et al, 2013;Lefkowitz & Elzinga, 2015). In the following section, the mechanisms of transformation were studied at the crystal scale, hypothesizing that an increased concentration of Mn 2þ led to an increased conversion of d-MnO 2 to synthetic feitknechtite without significant dissolution of d-MnO 2 .…”
Section: Mineralogical Evolutionsupporting
confidence: 87%
See 3 more Smart Citations
“…Such an evolution was consistent with previous studies (Elzinga, 2011(Elzinga, , 2016Lefkowitz et al, 2013;Lefkowitz & Elzinga, 2015). In the following section, the mechanisms of transformation were studied at the crystal scale, hypothesizing that an increased concentration of Mn 2þ led to an increased conversion of d-MnO 2 to synthetic feitknechtite without significant dissolution of d-MnO 2 .…”
Section: Mineralogical Evolutionsupporting
confidence: 87%
“…The present description of the vernadite-to-feitknechtite transformation, from macroscopic to crystal scales, is consistent with our current understanding of this transformation (Elzinga, 2011(Elzinga, , 2016Lefkowitz et al, 2013;Lefkowitz & Elzinga, 2015). One of the key findings is the major role of oriented aggregation in the nucleation and growth of feitknechtite from d-MnO 2 precursors.…”
Section: The Role Of Oriented Aggregation In Nanoparticle Growthsupporting
confidence: 87%
See 2 more Smart Citations
“…44 In addition, previous reports have shown that Mn(II) can react with birnessite and alter the XRD pattern of the birnessite. 43,47,48 In our case, we found that the XRD patterns of the birnessite before and after reaction with Gb1 are essentially identical (see SI), further indicating that little Mn(II) is produced during the reaction. Therefore, we propose that degradation of Gb1 by birnessite is the result of hydrolysis of the peptide bond catalyzed by the birnessite surface.…”
Section: Articlesupporting
confidence: 53%